Rebound Effect pada Circular Economy (CER): Narrative Literature Review - Wirya Wardaya; Ignatia Martha Hendrati; Putra Perdana (Journal of Economics Development Issues, 2025)
The purpose of this study is to provide an overview of the Rebound Effect (RE) in the context of the circular economy (CE). This study uses a narrative literature review to review and analyze scientific literature relevant to the topic of CER. Many approaches in CE are still dominated by an engineering perspective, namely seeing the world as a linear material flow system that can be transformed into a circular one without taking into account the complexity of the market and economy. Based on criticism and thoughts about the risks of the CE approach, a phenomenon called the Circular Economy Rebound (CER) emerged. CER occurs when circular activities, despite having a lower impact per unit, actually trigger an increase in total production and consumption, which ultimately reduces or even eliminates the expected environmental benefits. Based on the mapping of potential RE in CE, nine causes were found, while for the dimensions of CE implementation, 5 dimensions were found that cause RE both directly and indirectly. The method for measuring RE in CE found that RE can be measured at the micro, meso, macro and global aggregate levels with econometric techniques and Input-Output analysis.